The NTCP-inhibitor Myrcludex B: effects on bile acid disposition and tenofovir pharmacokinetics - Blank, Antje; Eidam, Annette; Hohmann, Nicolas; Burhenne, Jürgen; Meyer, Markus Robert; Meier, Katrin; Weiß, Johanna; Bruckner, Thomas; Urban, Stephan; Mikus, Gerd; Haefeli, Walter E. (Clinical pharmacology & therapeutics, 2018)
Myrcludex B acts as a hepatitis B and D virus entry inhibitor blocking the sodium taurocholate cotransporting polypeptide (SLC10A1). We investigated the effects of myrcludex B on plasma bile acid disposition, tenofovir pharmacokinetics, and perpetrator characteristics on cytochrome P450 (CYP) 3A. Twelve healthy volunteers received 300 mg tenofovir disoproxil fumarate orally and 10 mg subcutaneous myrcludex B. Myrcludex B increased total plasma bile acid exposure 19.2-fold without signs of cholestasis. The rise in conjugated bile acids was up to 124-fold (taurocholic acid). Coadministration of tenofovir with myrcludex B revealed no relevant changes in tenofovir pharmacokinetics. CYP3A activity slightly but significantly decreased by 29% during combination therapy. Myrcludex B caused an asymptomatic but distinct rise in plasma bile acid concentrations and had no relevant impact on tenofovir pharmacokinetics. Changes in CYP3A activity might be due to alterations in bile acid signaling. Long-term effects of elevated bile acids will require critical evaluation.